Republic of Korea : Staff Report for the 2006 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2006)
Korea has enjoyed strong growth owing to rapidly increasing exports and consumption. Potential growth is slowing as the population ages, whereas social polarization is growing. Korea should implement plans to build an advanced financial system and improve service productivity by opening the sector to more competition and enhancing small firms' access to finance. It should also address the prospective long-term deterioration of the fiscal position owing to population aging by tackling the health care and pension problems, and increase labor market flexibility.